Identifying Parental Feeding Patterns in a Spanish Sample of Toddlers Using a Latent Class Analysis - Mar Lozano‐Casanova; Silvia Escribano; Isabel Sospedra; Antonio Oliver‐Roig; Miguel Richart‐Martinez (Maternal and Child Nutrition)
ABSTRACT Parental feeding styles are an important factor influencing child development. Traditionally, they have been classified into four styles based on cut‐off points for responsiveness and demandingness. However, alternative methods, such as latent class analysis (LCA), allow for the detection of underlying homogeneous populations. The aims of this study are to: (a) identify different parental feeding styles in a Spanish sample using LCA; (b) explore the characteristics of the classes of different parenting styles, taking into account sociodemographic and psychological variables; and (c) compare the classification of parental feeding styles by assessment method: LCA versus the median split cut‐off point to determine high and low levels for each dimension. A cross‐sectional study (n = 774, including fathers and mothers of toddlers) was conducted to perform a one‐step LCA with covariates, using items that assess the demandingness and responsiveness feeding dimensions. Cross‐tabulations were performed to compare the use of LCA versus the median cut‐off point for assessing parental feeding styles/patterns. Four different patterns emerged from the LCA, characterised by high or moderate scores for responsiveness and varying scores for demandingness. These were labelled as the Moderately Authoritative, Authoritative, Moderate, and Indulgent classes. Mothers were more likely to belong to the Indulgent class, and high levels of parental stress increased the likelihood of parents belonging to the Moderate class. The classification of participants was not consistent between the two methods. Authoritarian and uninvolved feeding behaviours were not detected using LCA. In conclusion, gender and parental stress were factors that may help to explain the distribution of parents across feeding styles. These variables should therefore be considered when studying different populations. Furthermore, LCA could be utilised to design more accurate intervention strategies by helping to identify common needs among parents.